An update on hydroxyapatite/collagen composites: What is there left to say about these bioinspired materials?. Issue 5 (3rd December 2021) - Veiga, Anabela; Castro, Filipa; Rocha, Fernando; Oliveira, Ana L.
Abstract: Hydroxyapatite (HAp)/collagen‐based composite materials have been a constant in the development of bioinspired materials for bone tissue engineering. The most fundamental research works focus on combining HAp, due to its chemical similarity with the mineral component of bones, and collagen, which is the most abundant protein in the body. Modern studies have explored different two‐dimensional (2D) and 3D structures, in order to obtain biomaterials with specific physicochemical, mechanical, and biological characteristics that can be applied in distinct biomedical applications. However, as there is already so much work developed with these materials, it is crucial to question: what can still be done? What is the importance of current know‐how for the future of bioinspired materials? In this paper we intend to review and update the available methodologies to synthesize HAp/collagen composites, along with their characteristics. In addition, the future of these materials in terms of applications and their potential as a cutting‐edge technology is discussed.